Physiotherapy for patients following coronary artery bypass graft (CABG) surgery: limited uptake of evidence into practice - Filbay, S; Hayes, K; Holland, A (Taylor and Francis, 2012)
The efficacy of physiotherapy techniques used for patients following uncomplicated coronary artery bypass surgery (CABG) is well documented. Previous research showed that some of this evidence was not rapidly adopted into practice by cardiothoracic physiotherapists; however, there has been no recent evaluation of the uptake of evidence. Our aim was to identify current physiotherapy interventions in use for patients following uncomplicated CABG surgery. A survey was sent to senior cardiothoracic physiotherapists from all Australian and New Zealand hospitals that perform CABG surgery. Fifty-four surveys were returned (response rate 88%). The most common treatments used were mobilisation (94% of hospitals), range of motion exercises (79%), deep breathing and/or cough (77%), cardiovascular exercise (42%), and incentive spirometry (40%). Respondents with a bachelor or diploma in physiotherapy were more likely to implement deep breathing exercises or coughing than those who obtained a postgraduate degree (p = 0.045). Respondents perceived personal experience as the most influential factor on postoperative treatment choices. Physiotherapists treating patients following uncomplicated CABG surgery continue to use interventions such as deep breathing exercises that are not supported by best available evidence. Standardised guidelines may be required to better match clinical practice with current literature.